Space Doctrine of India. Issue 2 (1st September 2016) - Sachdeva, Gurbachan Singh
ABSTRACT: The tradition of promulgating military doctrines exists from time immemorial. In India, the same concept was adapted for civil purposes in the case of a nuclear doctrine. Herein, a space doctrine of India is proposed. From the beginning of space activities, India did not have an articulated, directive space policy. Nevertheless, India achieved successes in space activities ranging from indigenous launch to scientific probes to the Moon and Mars. Today, India is a space power of global standing and a space doctrine represents an authentic expression of India's stance on space governance and space activities. The doctrine suggested in this article is one of resolve of the state to dedicate itself to a committed vision of collective prosperity through space activities, collective welfare of humankind, equity sharing with all stakeholders, and sustainability in the use of the space environment. It is an authoritative and emphatic statement on intended uses of outer space, an almanac of governing practices, and an enabler of regulation and supervision of national space activities in outer space.